2021
DOI: 10.1186/s12985-021-01517-z
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo studies reveal α-Mangostin, a xanthonoid from Garcinia mangostana, as a promising natural antiviral compound against chikungunya virus

Abstract: Background Chikungunya virus (CHIKV), a serious health problem in several tropical countries, is the causative agent of chikungunya fever. Approved antiviral therapies or vaccines for the treatment or prevention of CHIKV infections are not available. As diverse natural phenolic compounds have been shown to possess antiviral activities, we explored the antiviral activity of α-Mangostin, a xanthanoid, against CHIKV infection. Methods The in vitro pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 46 publications
1
49
0
Order By: Relevance
“…In the present study, though the antiviral activity of α-Mangostin was assessed against only DENV-2, the compound needs to be tested against the other serotypes as well. Our earlier study had shown that α-Mangostin inhibits chikungunya virus (CHIKV) in infected C57BL/6 mice [ 43 ]. Since CHIKV and DENV infection results in similar types of clinical symptoms, α-Mangostin might be a promising candidate for treatment of dengue-like illness.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, though the antiviral activity of α-Mangostin was assessed against only DENV-2, the compound needs to be tested against the other serotypes as well. Our earlier study had shown that α-Mangostin inhibits chikungunya virus (CHIKV) in infected C57BL/6 mice [ 43 ]. Since CHIKV and DENV infection results in similar types of clinical symptoms, α-Mangostin might be a promising candidate for treatment of dengue-like illness.…”
Section: Discussionmentioning
confidence: 99%
“…In general, most of the studies use C57BL/6J wild type (WT) mice and CHIKV inoculation might occur from newborns at just few days after birth up to elderly animals of up to 48 weeks old. Likewise, virus titer can range from 10 2 to 10 8 plaque-forming unit (pfu)/ml (Gardner et al, 2010;Bosco-Lauth et al, 2015;Uhrlaub et al, 2016;Abdelnabi et al, 2018;Arévalo et al, 2019;Jain et al, 2019;Adam et al, 2021;Patil et al, 2021). Therefore, it is clear that the existence of a diversity of CHIKV rodent models and not surprisingly divergent outcomes is observed in each of them.…”
Section: Rodent Modelmentioning
confidence: 99%
“…In contrast, after subcutaneous injection of 2 × 10 7 pfu/ml in 8-week-old C57BL/6J mice in the hind limbs, it was found replicating virus particles only until Uhrlaub et al, 2016;Arévalo et al, 2019;Jain et al, 2019 Anti-CHIKV treatment WT C57BL/6, C1q −/− , FcRγ −/− Limitation on CHIKV infection. Abdelnabi et al, 2018;Fox et al, 2019;Patil et al, 2021 Arthritis WT C57BL/6, ISG15 −/− , UbE1L −/− , MHCII / , IFNγ −/− , Sting gt/gt , CCR2 −/− CHIKV arthritis signature. Gardner et al, 2010;Werneke et al, 2011;Nakaya et al, 2012;Poo et al, 2014a;Geng et al, Wang et al, 2011;Arévalo et al, 2019;Campos et al, 2019;López-Camacho et al, 2019;Chen et al, 2020;Adam et al, 2021 Chronic/Persistent model WT C57BL/6, CD8 α −/− , Batf3 −/− , Wdfy4 −/− , Rag1 −/− , µMT C57BL/6; Golden hamster Viral persistence in joint tissues.…”
Section: Rodent Modelmentioning
confidence: 99%
“…In vitro prophylactic effect of α‐mangostin (extracted from the pericarps of mangosteen) was significantly inhibited the replication of CHIKV in Vero E6 cells with the 100% reduction of virus titer at 8 μM concentration under cotreatment condition (Patil et al., 2021 ). Also, reduction of CHIKV replication in serum and muscles of infected mice models showed nearly 99% of reduction in CHIKV RNA copies with low and high dose of α‐mangostin.…”
Section: Introductionmentioning
confidence: 99%
“…Also, reduction of CHIKV replication in serum and muscles of infected mice models showed nearly 99% of reduction in CHIKV RNA copies with low and high dose of α‐mangostin. The molecular docking study revealed that α‐mangostin interacts with the E2‐E1 heterodimeric glycoprotein and the outcomes suggest that α‐mangostin can possibly inhibit the replication of CHIKV infection through multiple target proteins (Patil et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%